2017
DOI: 10.3389/fonc.2017.00306
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Transport and Mitochondrial Metabolism in Cancer Cell Growth

Abstract: The concept that cancer is a metabolic disease is now well acknowledged: many cancer cell types rely mostly on glucose and some amino acids, especially glutamine for energy supply. These findings were corroborated by overexpression of plasma membrane nutrient transporters, such as the glucose transporters (GLUTs) and some amino acid transporters such as ASCT2, LAT1, and ATB0,+, which became promising targets for pharmacological intervention. On the basis of their sodium-dependent transport modes, ASCT2 and ATB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
146
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 96 publications
0
146
0
1
Order By: Relevance
“…Glutamine metabolism contributes to energy production, macromolecular synthesis, and redox homeostasis, and is essential for survival of some cancer cells that have become addicted to glutamine 10,11,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine metabolism contributes to energy production, macromolecular synthesis, and redox homeostasis, and is essential for survival of some cancer cells that have become addicted to glutamine 10,11,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different tumors, including melanoma, have demonstrated that L-Gln utilization correlates with: (a) increased mitochondrial glutaminase 2 activity that is dependent on Rho GTPases and NF-kB activity; and (b) oncogenic levels of Myc which induce a transcriptional program that promotes glutaminolysis and trigger cellular addiction to L-Gln as a bioenergetic substrate (Scalise et al, 2017). Tumors with high rates of glutamine uptake and metabolism can behave as glutamine traps, depleting host glutamine stores, producing glutamate rapidly, and resulting in cachexia (Klimberg and McClellan, 1996).…”
Section: Systemic Mechanismsmentioning
confidence: 99%
“…Although glutamine was previously considered to be a non-essential amino acid in normal organisms, it is essential for rapid proliferation and growth of most cancer cells (De Vitto et al, 2016). Glutamine metabolism can provide intermediate metabolites of biosynthesis of macromolecules for TCA pathway and play a 'reinforcing role' in the TCA cycle (Scalise et al, 2017;Akins et al, 2018). In addition, glutamine also participates in the maintenance of cell redox homeostasis (DeBerardinis and Cheng, 2010).…”
Section: Introductionmentioning
confidence: 99%